Lysine221 is the general base residue of the isochorismate synthase from Pseudomonas aeruginosa (PchA) in a reaction that is diffusion limited - Meneely, Kathleen M. (2013)
The isochorismate synthase from Pseudomonas aeruginosa (PchA) catalyzes the conversion of chorismate to isochorismate, which is subsequently converted by a second enzyme (PchB) to salicylate for incorporation into the salicylate-capped siderophore pyochelin. PchA is a member of the MST family of enzymes, which includes the structurally homologous isochorismate synthases from E. coli (EntC and MenF) and salicylate synthases from Yersinia enterocolitica (Irp9) and Mycobacterium tuberculosis (MbtI). The latter enzymes generate isochorismate as an intermediate before generating salicylate and pyruvate. General acid – general base catalysis has been proposed for isochorismate synthesis in all five enzymes, but the residues required for the isomerization are a matter of debate, with both lysine221 and glutamate313 proposed as the general base (PchA numbering). This work includes a classical characterization of PchA with steady state kinetic analysis, solvent kinetic isotope effect analysis and by measuring the effect of viscosogens on catalysis. The results suggest that isochorismate production from chorismate by the MST enzymes is the result of general acid – general base catalysis with a lysine as the base and a glutamic acid as the acid, in reverse protonation states. Chemistry is determined to not be rate limiting, favoring the hypothesis of a conformational or binding step as the slow step.